The Vegetation of Northern Manitoba V. Establishing the Major Zonation - Ritchie, J.C. (ARCTIC, 1960)
Maps the vegetation zones north of 56 N. from field studies during 1954-59, and vertical air photographs. The zones are defined as geographical regions occupied by a number of plant communities and characterized by the prevalence of one, or by a particular proportion of two or more communities. Four are delineated for the Canadian Shield: tundra, forest tundra, open coniferous forest, closed coniferous forest, and four for the Hudson Bay Lowlands: transitional, moss muskeg, treeless bog, lowland complex. Vegetation, physiography, and photographic appearance (tone, texture, structure) are discussed for each zone; detailed descriptions of the vegetation are given in other papers of this series (supra, No. 47602, 54326).